PENGARUH PUPUK HIJAU TANAMAN KEMBANG BULAN (Tithonia diversifolia) DAN PUPUK KANDANG TERHADAP PRODUKSI TANAMAN EKINASE (Echinacea purpurea) - Dian Susanti; Harto Widodo; Erri S. Hartanto (Pusat Penelitian dan Pengembangan Perkebunan, 2017)
Echinaceae is introduced medicinal plant as immunomodulator. The high demand of echinaceae as raw material for immunomodulatory herbal medicine by the industries, requires the increase in quantity and quality of cultivated echinaceae. Thus, the use of fertilizer is necessary. However, to ensure the safety of raw materials for herbal medicine industry, the use of organic fertilizer becomes one of the important components. Organic fertilizer used can be in the form of solid fertilizer such as dung manure, compost and green manure. Various plants can be utilized as a source of green manure such as Tithonia diversifolia, because of its high N content. The aim of this research was to evaluate the effect of the dosage of dung manure and green manure from T. diversifolia on echinaceae biomass and echinacoside contents. The research was arranged in Factorial Randomized Block Design with two treatments, three dosages of dung manure (P) 0; 2.5; 5 ton.ha-1, and three dosages of green manure from T. diversifolia (T) 0; 10 and 20 ton.ha-1. The treatment combinations were repeated three times. The results showed that there was no interaction between T. diversifolia green manure and dung manure usage. The use of T. diversifolia fertilizer alone was not evidently increased the fresh weight of biomass at 20 ton.ha-1. The use of T. diversifolia and dung manure showed no significant effect on echinacoside content.